O sigilo bancário e a fraude fiscal - Monteiro, Ricardo Filipe Casquinha (2015)
Tax evasion and fraud threaten the economic and social objectives of modern tax systems, precluding the state funding for the satisfaction of collective needs and the fair distribution of wealth, being a violation of basic principles and values of our society. In tax law, to give tax administration the necessary powers to supervise and control the information provided by taxpayers and combat tax evasion and fraud, over the last years the grounds for a derogation of bank secrecy without judicial authorization have been extended, which raises some constitutional compatibility issues. Similarly, this tendency of making this legal regime more flexible and increasing automatic exchange of information has been followed by the European Union and the international community. Banking secrecy, as a professional secrecy, is an instrument to protect the right to privacy but also appears as an anti-abuse and repressive mechanism of evasive and fraudulent behaviors. Because of the conflict of interests will always be necessary to make a practical agreement between them, ensuring the legality and the due guarantees of the taxpayers but also an effective way to combat tax evasion and fraud. Bank secrecy cannot be one method to, behind the right to privacy, taxpayers practice illegal activities. But the practice of these irregular conducts also does not justify a total annihilation of the right to banking secrecy, uncovering all documents and bank information’s. Although considering the legislative changes, the administrative derogation of bank secrecy will always be what the tax administration does of it.